Measuring patient safety culture: an assessment of the clustering of responses at unit level and hospital level. Issue 4 (3rd August 2009) - Smits, M; Wagner, C; Spreeuwenberg, P; van der Wal, G; Groenewegen, P P
Abstract : Objectives: To test the claim that the Hospital Survey on Patient Safety Culture (HSOPS) measures patient safety culture instead of mere individual attitudes and to determine the most appropriate level (individual, unit or hospital level) for interventions aimed at improving the culture of patient safety. Methods: National patient safety culture data were used from 1889 hospital staff working at 87 units in 19 hospitals across The Netherlands. The multilevel structure of the variation of responses to the 11 dimensions of the questionnaire was explored by fitting three-level random intercept models: individual, unit and hospital level. Results: The unit level was the dominating level for the clustering of responses to the 11 dimensions. Intraclass correlations (ICC) at unit level ranged from 4.3 to 31.7, representing considerable higher-level variation. For three dimensions of patient safety culture, there was significant clustering of responses at hospital level as well: (1) Feedback about and learning from error, (2) Teamwork across hospital units and (3) Non-punitive response to error. Conclusions: At a conceptual level, the detection of clustering of responses within units and hospitals confirms the claim that the HSOPS measures group culture and not just individual attitudes. In addition, the results have implications for interventions on patient safety culture. Improvement efforts should be directed at their most relevant organisational level. In general, improvement efforts on patient safety culture should be addressed at the unit level, rather than the individual or hospital level.